NMR structural elucidation of dehydrodimers resulting from oxidation of 5-O-caffeoylquinic acid in an apple juice model solution. (15th March 2022) - Castillo-Fraire, Claudia Mariana; Pottier, Sandrine; Bondon, Arnaud; Salas, Erika; Bernillon, Stéphane; Guyot, Sylvain; Poupard, Pascal
Highlights: Seven caffeoylquinic acid (CQA) dehydrodimers were analysed using 1 H and 13 C NMR. Four molecular skeletons of caffeoylquinic acid (CQA) dehydrodimers were elucidated. Six compounds exhibited dihydrobenzofuran, benzodioxane or dihydronaphtalene nuclei. A new CQA dehydrodimer showing a symmetric dicatechol skeleton was identified. Two structure hypotheses were formulated for this new molecule identified. Abstract: During apple juice and cider-making processes, phenolic compounds undergo enzymatic oxidation. 5- O -caffeoylquinic acid (CQA) is one of the major hydroxycinnamic acid derivatives and it is the preferential substrate for polyphenol oxidase (PPO) in apple juices. Consequently, CQA dehydrodimers (MW 706 Da) are among the main products resulting from CQA oxidation. CQA dehydrodimers were previously synthesized in a biomimetic apple juice model solution. Following their purification and characterization using UV–Visible spectra and mass spectrometry, the structures of seven CQA dehydrodimers were elucidated using 1 H and 13 C one- and two-dimensional NMR spectroscopy. Six of them exhibited dihydrobenzofuran, benzodioxane, or dihydronaphtalene skeletons, which are caffeicin-like structures. Interestingly, a new dehydrodicaffeoyldiquinic acid molecule was also characterised for which two novel structures showing a symmetric dicatechol skeleton were also proposed.